Professional development for teachers: Introducing sport education in Russian schools - Sinelnikov, O. (Research Quarterly for Exercise and Sport, 2009)
The professional development may have a positive effect on teacher knowledge, motivation and improve students' learning (Armour & Evans, 2006), however, single workshops unconnected to a school do not provide adequate professional development in any topic (NPEAT, 1999).